Ballistics of 17th century muskets - Miller, David P. (Cranfield University, 2010)
This Project is an investigation to determine the position that a 17th Century musket ball was fired from a musket, when given the position it was found on the battlefield. Prior to this research the main concerns with making predictions were considered to be associated with the deformed shape of the musket balls affecting their drag coefficient and therefore, their distance to ground impact. The distance they would continue after impact due to bounce and roll was unknown. Previous research has been used and built upon to recreate the conditions of the English Civil War as accurately as possible. It was found that the average distance to ground impacts were in good agreement with predictions using the drag coefficient for a sphere showing that the distorted shape resulting from the firing process of the musket ball made little difference to its drag coefficient in the majority of cases. However, the distance travelled after the first ground impact greatly exceeded expectations, with the musket balls almost doubling the total average distance to their final resting positions - an increase of 81%. From these findings the initial factors thought to have had high relevance to the final resting position of the musket ball (velocity variation and drag co-efficient) become less significant and factors such as ground hardness become more prominent. The knowledge gained during this investigation will re-establish more accurate information to be obtained on the firing positions of opposing forces during conflicts in the English Civil War.
Keywords: English Civil War; Musket; Ballistics; History and warfare